Scientific Paper Writing Training: A Boost to Scientific Publication at Institut Agama Islam Nahdlatul Ulama Bangil - Aziz, Abdul; Mulyanto, Angga Dwi; Setyowati, Ernaning (JRCE (Journal of Research on Community Engagement), 2024)
Institut Agama Islam Nahdlatul Ulama Bangil is a private university in East Java, Indonesia, affiliated with Nahdlatul Ulama. Despite its commitment to quality education based on Islamic values, the university's lecturers face challenges in publishing scientific articles. Previous research underscores the importance of training, workshops, and technology tools in improving lecturers' scientific publication skills. This article proposes a Participatory Action Research approach for scientific article writing training, involving issue identification, active lecturer involvement, planning, implementation, and evaluation. This approach fosters collaboration and enhances lecturers' scientific writing abilities. Similar successful approaches in other institutions highlight the potential positive outcomes of such training. The goal is to empower lecturers, boost publication rates, and contribute to individual and institutional advancement.